Pola Pendidikan Islam di Pondok Pesantren Mahasiswa Miftahul Khoir Bandung dalam Membentuk Kepribadian Islami - Tatang Hidayat .; Ahmad Syamsu Rizal; Fahrudin . (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2018)
AbstractThe purpose of this present study is to describe the Islamic education system at Miftahul Khoir University Student Islamic Boarding School in the process of establishing Islamic personality. This present study employed a descriptive method and a qualitative approach. Based on the results of the study, the Miftahul Khoir University Student Islamic Boarding School was considered as the Salafi Islamic Boarding School group. In fact, it was indicated by the establishment of religious understanding which was adopted from Miftahul Huda Islamic Boarding School, Tasikmalaya. The purpose of Islamic education at Miftahul Khoir University Student Islamic Boarding School is to raise up leader cadres leaders of people who have Islamic personality and develop the religion of Islam in accordance with their field of expertise. Keywords: System, Islamic Education, Miftahul Khoir University Student Islamic Boarding School, Bandung, and Islamic Personality.AbstrakTujuan penelitian ini untuk mendeskripsikan pola pendidikan Islam di Pondok Pesantren Mahasiswa Miftahul Khoir dalam membentuk kepribadian Islami. Penelitian ini menggunakan metode deskriptif dan pendekatan kualitatif. Berdasarkan hasil penelitian, Pondok Pesantren Mahasiswa Miftahul Khoir termasuk ke dalam kelompok pesantren salafi yang dari segi pemahaman keagamaan menginduk kepada Pondok Pesanren Miftahul Huda Tasikmalaya. Tujuan pendidikan Islam di Pondok Pesantren Mahasiswa Miftahul Khoir memiliki ciri khas dalam mewujudkan kader pemimpin umat yang memiliki kepribadian Islami dan mengembangkan dinul Islam sesuai dengan kemampuan ilmu yang diperolehnya. Kata Kunci: Pola, Pendidikan Islam, PPM Miftahul Khoir Bandung, dan Kepribadian Islami